FAKTOR RISIKO YANG MEMPENGARUHI FLAT FOOT PADA ANAK: - Widiani, Ni Kadek; Pramita, Indah; Vittala , Govinda (Kinetic and Physiotherapy Comprehensive, 2024)
Background: The condition of flat feet in children will affect activity, development, and weight management. Even though there are often no symptoms, if the condition leads to a severe stage, it will interfere with the function of the feet. The impacts that can be caused by flat feet include walking that is not good, being quickly tired, impaired agility, and poor balance, which affects children's activities. Therefore, knowing the factors that can affect flat feet is necessary. This study aimed to determine the risk factors for flat feet in children. Methods: The study used a literature review design using secondary data from published literature. The literature search was conducted online through PubMed, ScienceDirect, and Google Scholar, using the keywords “flat foot”, “plantar index”, and “risk factors”, which were selected based on inclusion and exclusion criteria. Results: Aged 6-12 years are described as having a higher risk of experiencing flat feet. The male sex has a greater risk than women, the use of closed footwear also has a greater risk, and low physical activity is one of the risk factors. Besides that, being overweight and obese can increase the risk of flat feet. Conclusion: The strongest risk factor for flat feet was age, which was also influenced by gender, footwear shape, activity, and nutritional status.